Black Panther spellbound - Smith, Ronald L. (Ronald Lenard), 1959- (Marvel Press, 2021)
"I'm T'Challa. The Prince of Wakanda. Son of T'Chaka. And one day, I will wear the mantle. Thirteen-year-old T'Challa can't wait to go back to America to visit his friends Sheila and Zeke, who are staying with Sheila's grandmother in Beaumont, a small Alabama town, over their summer break. He's thrilled to be on vacation away from his duties as the Prince of Wakanda for a few weeks, and he's taking full advantage of his access to the amazing food and the South's rich history. But as T'Challa continues to explore the town, he finds that a man who goes by the ordinary name of Bob happens to be everywhere he is -- and T'Challa begins to think it's no coincidence."--From inside cover flap.